Voltammetric Determination of Cymoxanil and Famoxadone at Different Types of Carbon Electrodes. Issue 5 (15th December 2015) - Bavol, Dmytro; Zima, Jiri; Barek, Jiri; Dejmkova, Hana
Abstract: Differential pulse voltammetry (DPV) at a carbon fibre rod electrode (CFRE) and a capillary carbon paste electrode (CPE) have been used for the determination of pesticides cymoxanil and famoxadone, respectively. In the cathodic potential range, optimum conditions were found for the determination of cymoxanil by DPV at CFRE at pH 4 with limit of quantification ( L Q ) of 5.9×10 −7  mol L −1 . In the anodic area, determination of famoxadone by DPV at CPE was performed at optimum pH 2 with L Q =1.4×10 −7  mol L −1 . Practical applicability of the newly developed methods was verified on spiked samples of river water and soil. Abstract :